The Role of Educational Methods in Teaching Students to Think Independently in Literature Lessons (Texas Journal of Philology, Culture and History, 2023)
This article explains what the concept of "independent thinking" is and how important it is in forming a well-rounded person. Different methods and information about the thinking process, in particular, its type of independent thinking, are described